Resurrection and Heritage: Research on the Application of AIGC in the Preservation of Ancient Books in Archives - MA, GUAN; Pu, Zhenyan (International Journal of Advanced AI Applications, 2025)
This study outlines the methods for protecting ancient books in archives, elaborates on the basic principles and key technologies involved in generative artificial intelligence, and explores the specific applications of generative artificial intelligence in the protection of ancient books in archives from three aspects: primary protection, regenerative protection, and inheritance protection. Taking the generation of ancient book illustrations as an example, the implementation process of using generative artificial intelligence to carry out ancient book protection in archives is analyzed. Based on five aspects: formulating and improving policies and regulations, constructing cooperation mechanisms and approaches, ensuring data integrity and security, strengthening technical support and innovation, and establishing evaluation and feedback mechanisms, a strategy for the protection of ancient books in archives based on generative artificial intelligence is proposed.